Advances in Pacific Basin business economics and finance, Vol. 5 - Lee, Cheng F.; Yu, Min-Teh (Advances in Pacific Basin business, economics and finance)
Prelims -- Insurance contracts and derivatives that substitute for them: how and where should their systemic and nonperformance risks be regulated? -- A further equity premium puzzle -- Credit crunch and saving glut in Taiwan: empirical evidences -- Stock market activities and industrial production growth: evidence from 20 international markets -- Bank capital standards and subordinated debt prices -- Accounting fraud, audit fees, and government intervention in China -- The employment status of marriage immigrants in Taiwan -- Human capital investment inequality and rural - urban income gap: evidence from China -- An operational efficiency analysis for organizational consolidation in the business operating departments of a case telecom company -- Financial market variables and housing prices: evidence of ASEAN+2 -- Index